Water and water-related phenomena in the Old Testament wisdom literature : an eco-theological exploration - Kavusa, Kivatsi Jonathan (London ; New York, NY, USA : T&T CLark, 2019)
"Kivatsi Jonathan Kavusa addresses a gap in the field of ecological readings of the Old Testament, exploring the theme of water in the Wisdom books, including the often-ignored deuterocanonical works. Kavusa focuses on both the negative and positive potential of water, drawing in particular on four of the Earth Bible principles: intrinsic worth, interconnectedness, voice, and purpose. Kavusa begins with a summary of the extant studies and literature reviews on water and water-related motifs in the Old Testament. He then analyses the books of Job, Proverbs, Ecclesiastes and the Deutero-canonical wisdom, examining the various references to water as life-giving or life-threatening entities, and expanding upon the themes of water management and sustainability, the intrinsic worth of nature and the unpredicatable, chaotic state of water. This volume concludes with several insights for ecological responsibility and valuable wisdom for an eco-theological perspective, both in Kavusa's African context and with a more universal application."--Bloomsbury publishing.
List of Tables Foreword by Willie van Heerden - University of South Africa, South Africa Acknowledgments Abbreviations Chapter 1: Introduction Chapter 2: Previous Studies on Water and Water-Related Phenomena in the Old Testament Chapter 3: Water and Water-Related Phenomena in the Book of Job Chapter 4: Water and Water-Related Phenomena in the Book of Proverbs Chapter 5: Water and Water-Related Phenomena in the Book of Qoheleth Chapter 6: Water and Water-Related Phenomena in the Deutero-Canonical Wisdom Books -- Chapter 7: Conclusions - Eco-Theological Implications of the Study Appendix A: References to Water and Water-Related Phenomena in the Old Testament Wisdom Books Appendix B: References to the Life-Giving and Life-Threatening Potential of Water and Water-Related Phenomena Bibliography.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Includes bibliographical references and index.
Also issued in print.
Electronic reproduction.
Keywords: Water in the Bible; Bible. -- Criticism, interpretation, etc